Incidence and Related Factors of Depression in Adolescents with Cancer - Banki, Yasaman; Abedin, Ali Reza (Richtmann Publishing, 2012)
This study aimed to investigate the prevalence of depression among adolescents with cancer. A sample of 174adolescents diagnosed with cancer along with one of their parents, respectively completed Beck Depression Inventory forPrimary Care (BDI-PC) and Beck Depression Inventory (BDI) as well as a demographic questionnaire. Results revealed that29.9% of adolescent participants were diagnosed with depression disorder. Furthermore, there were positive correlationsbetween adolescent depression with parents’ depression, cancer relapse, and number of children in the family. However nosignificant correlation was indicated between adolescent depression with adolescents’ age, gender, the age when diagnosis wasmade, duration of illness, amount and kind of treatment methods, intensity of disease, and family income.